Effect of the increase in the Minimum Wage on the employment level - Jiménez-Bandala, Carlos Alberto; Chiatchoua, Cesaire; Andrade, Luis Antonio; Guadarrama, Alma; Meneses-Ruiz, Dulce Maria; Peralta, José Daniel; Márquez, Ian; Sánchez, Enrique; Matus, Edgar; Arellano, Diana (Revista Internacional de Salarios Dignos, 2020)
Based on the statistics provided by the IMSS, the number of jobs was not affected by the increase in the minimum wage of January 2019. The dynamics of job creation were also not affected by the salary increase, either at the national level or at the disaggregated level in the north of the country. The analysis of the statistical results does not coincide with those obtained by BANXICO and methodological errors of the central bank study are highlighted.